The Role Of Brand Image And Perceived Quality In Mediating Social Media Marketing On Repurchase Intention (Enjang Coffee Jepara Customer Study) - Septyani, Mirna Dyah; Roosdhani, Mohamad Rifqy (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In the rapidly evolving digital age, social media marketing platforms in particular. This encourages business owners to compete in advertising and creating engaging content in the e-commerce and digital marketing environment. The method used is quantitative with 100 samples analysed by SEM with Smart-PLS version 4.0. The test uses outer model test, inner model test, mediation test and hypothesis testing. The validity test results provide a loading factor value> 0.7 and an AVE value> 0.5 declared valid. The reliability test provides compas reliability and Cronbach's alpha> 0.7 which is considered reliable. It can be concluded that the effect of social media marketing on brand image is positive and significant, the effect of social media marketing on perceived quality is positive and significant, and the effect of brand image on repurchase intention is positive and significant. the effect of perceived quality on repurchase intention is positive and significant. The mediation test shows that repurchase intention is partially mediated by social media marketing variables which are mediated by brand image and perceived quality.